Map Construction Of Simple Sequence Repeat Developed For Introgression Philippine Downy Mildew Resistance Gene In Maize - D. Ruswandi; D. M. Hautea; A. M. Salazar; R. M. Lantican; A. L. Carpena; A. D. Raymundo (Zuriat, 2001)
Simple sequence repeats (SSRs) is an important DNA markers for mapping plant genomes particularly in mapping quantitative trait loci (QTL). To identify and map SSR markers for introgression resistance gene against Peronosclerospora philippinensis in maize, the parental materials (P 345 and Pi 23) together with 142 genotypes of BC1F1 of Pi 23 ×P 345 population were used. A total of 50 SSR markers were genotyped. However, only thirty-three markers were integrated into a molecular map together with RFLP and RGA markers. A molecular map of SSR was successfully constructed together with RFLP and RGA into 10 chromosomes. It covered a total map length of 1822 cM with an average distance of 18.22 cM between markers.